The Coiled‐Coil Domain Containing 80 (ccdc80) Gene Regulates gadd45β2 Expression in the Developing Somites of Zebrafish as a New Player of the Hedgehog Pathway. Issue 4 (April 2015) - Della Noce, Isabella; Carra, Silvia; Brusegan, Chiara; Critelli, Rosina; Frassine, Andrea; De Lorenzo, Carlo; Giordano, Antonio; Bellipanni, Gianfranco; Villa, Erica; Cotelli, Franco; Pistocchi, Anna; Schepis, Filippo
<x xml:space="preserve">Abstract</x> The Coiled‐Coil Domain Containing 80 (CCDC80) gene has been identified as strongly induced in rat thyroid PC CL3 cells immortalized by the adenoviral E1A gene. In human, CCDC80 is a potential oncosoppressor due to its down‐regulation in several tumor cell lines and tissues and it is expressed in almost all tissues. CCDC80 has homologous in mouse, chicken, and zebrafish. We cloned the zebrafish ccdc80 and analyzed its expression and function during embryonic development. The in‐silico translated zebrafish protein shares high similarity with its mammalian homologous, with nuclear localization signals and a signal peptide. Gene expression analysis demonstrates that zebrafish ccdc80 is maternally and zygotically expressed throughout the development. In particular, ccdc80 is strongly expressed in the notochord and it is under the regulation of the Hedgehog pathway. In this work we investigated the functional effects of ccdc80‐loss‐of‐function during embryonic development and verified its interaction with gadd45β2 in somitogenesis. J. Cell. Physiol. 230: 821–830, 2015. © 2014 Wiley Periodicals, Inc.